2020
DOI: 10.1101/2020.07.02.184218
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Urine metabolomics of rats with chronic atrophic gastritis

Abstract: AbstractBackground/Aim: To use liquid chromatography-mass spectrometry (LC-MS) to identify endogenous differential metabolites in the urine of rats with chronic atrophic gastritis (CAG). Materials and Methods: Methylnitronitrosoguanidine (MNNG) was used to produce a CAG model in Wistar rats, and HE staining was used to determine the pathological model. LC-MS was used to detect the differential metabolic profiles in rat urine. Diversified analysis was performed by the statistica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Some studies have shown that histidinol has the effect of reducing gastric acid and reducing gastrointestinal pain. In addition, it can also inhibit the proliferation and migration of lung cancer cells, thus play an anti-tumor role [20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that histidinol has the effect of reducing gastric acid and reducing gastrointestinal pain. In addition, it can also inhibit the proliferation and migration of lung cancer cells, thus play an anti-tumor role [20][21].…”
Section: Discussionmentioning
confidence: 99%